239 Setting Bones and Getting Home: The Impact of a New Orthogeriatric Service. (16th September 2019) - Murphy, Robert; Reddin, Catriona; Dempsey, Aoife; Kissane, Bláithín; Waters, Ruairi; Walsh, Thomas; O'Keeffe, Shaun; Mulkerrin, Eamon; Robinson, Stephanie; Egan, Ciara; Byrne, Fergus; O'Donnell, Martin; et al.
Abstract: Background: Orthogeriatric services have been shown to improve quality of care for older patients post hip fracture and have an impact on length of stay (LOS), both acutely and in the rehab setting (1) but other key performance indicators (KPIs) have not been examined in detail. Methods: Data was prospectively collected on all hip fracture patients seen by the Orthogeriatric service from Aug 2018-Feb 2019 and was retrospectively compared with patients admitted with hip fractures from Aug 2017-Feb 2018. We examined KPIs including LOS on the orthopaedic ward, rehab admissions, rehab LOS, new nursing home (NH) admissions. We compared the proportions discharged directly home instead of to convalescence, and conducted a preliminary cost benefit analysis. Results: Similar numbers of patients were seen in each time period (n=146 v n=139). Mean reduction in LOS on the orthopedic ward was 3.5 days (15.5 days vs 19 days). The proportion of patients admitted to rehabilitation increased from 8.8% to 17.5% (p = 0.02). Patients got to rehabilitation faster and for those patients who availed of rehabilitation they had significantly shorter total length of stays (51.1 days vs 71.6 days, p=0.029). Fewer patients went to convalescence. Although not statistically significant there was a trend towards an increased proportion of patients discharged directly home (32.7% to 43.6%) and less new nursing home admissions (6.8% vs 8.4%). A cost benefit analysis incorporating shortened acute and rehab LOS and a reduction in spending on convalescence resulted in a projected saving of €480, 390 over a six month period. Conclusion: Introduction of OrthoGeriatric services has improved care for older people with hip fractures and has resulted in positive improvements to KPIs, resulting in meaningful improvements in clinical outcomes for patients in a cost effective manner. Monies saved should be redirected into further developing orthogeriatric services.